Receptor-mediated mitophagy in yeast and mammalian systems - Liu, Lei; Sakakibara, Kaori; Chen, Quan; Okamoto, Koji (Cell research, 2014)
Mitophagy, or mitochondria autophagy, plays a critical role in selective removal of damaged or unwanted mitochondria. Several protein receptors, including Atg32 in yeast, NIX/BNIP3L, BNIP3 and FUNDCI in mammalian systems, directly act in mitophagy. Atg32 interacts with Atg8 and Atgll on the surface of mitochondria, promoting core Atg protein assembly for mitophagy. NIX/BNIP3L, BNIP3 and FUNDC1 also have a classic motif to directly bind LC3 （Atg8 homolog in mammals） for activation of mitophagy. Recent studies have shown that receptor-mediated mitophagy is regulated by reversible protein phosphorylation. Casein kinase 2 （CK2） phosphorylates Atg32 and activates mitophagy in yeast. In contrast, in mammalian cells Src kinase and CK2 phosphorylate FUNDC1 to prevent mitophagy. Notably, in response to hypoxia and FCCP treatment, the mitochondrial phosphatase PGAM5 dephosphorylates FUNDC1 to activate mitophagy. Here, we mainly focus on recent advances in our understanding of the molecular mechanisms underlying the activation of receptor-mediated mitophagy and the implications of this catabolic process in health and disease.